VARIABLES ALEATORIAS EN LA GESTIÓN EMPRESARIAL, SIMULACIÓN - Hermenejildo Chávez, María (2010)
In this article I present quantitative techniques to simulate a non-Uniform random-variables generator whose values distribute following a known (or unknown) probability distribution. And only when this isn’t possible with one of the presented methods, I will work the simulation empirically. Also, I present applications in the business of different probability distributions and its profiles for specific values of its parameters with the objective that the reader can identify the curve could represent to the random variable before applying a method. Like a example I show a graphic with statistical results that the generated dates distribute really as the dates of the original sample. In this way, the reader can use this information in a dynamic system of simulation processes with discrete events which represent a real system.